Role of MOTS-c in the regulation of bone metabolism - Yi, Xuejie; Hu, Guangxuan; Yang, Yang; Li, Jing; Jin, Junjie; Chang, Bo (Frontiers in Physiology, 2023)
MOTS-c, a mitochondrial-derived peptide (MDP), is an essential regulatory mediator of cell protection and energy metabolism and is involved in the development of specific diseases. Recent studies have revealed that MOTS-c promotes osteoblast proliferation, differentiation, and mineralization. Furthermore, it inhibits osteoclast production and mediates the regulation of bone metabolism and bone remodeling. Exercise effectively upregulates the expression of MOTS-c, but the specific mechanism of MOTS-c regulation in bone by exercise remains unclear. Therefore, this article reviewed the distribution and function of MOTS-c in the tissue, discussed the latest research developments in the regulation of osteoblasts and osteoclasts, and proposed potential molecular mechanisms for the effect of exercise on the regulation of bone metabolism. This review provides a theoretical reference for establishing methods to prevent and treat skeletal metabolic diseases.